The view at the zoo - Bostrom, Kathleen Long.; Francis, Guy (Nashville, Tenn. : Ideals Children's Books, 2010)
Illustrations and rhyming text provide a glimpse of a day at the zoo as experienced by the animals that live there.
Kirkus Review
Kirkus Review, March 2011
1.7
K-3
K-3
Keywords: Animals -- Juvenile fiction; Zoo animals -- Juvenile fiction; Zoos -- Juvenile fiction; Animals -- Fiction; Stories in rhyme; Zoo animals -- Fiction; Zoos -- Fiction; Animals -- Fiction; Stories in rhyme; Zoo animals -- Fiction; Zoos -- Fiction; Picture books for children